Effect of sintering temperature on the microstructure and mechanical properties of the Ti-2.5Zr alloy. (15th January 2021) - Alhazaa, Abdulaziz; Assaifan, Abdulaziz; Hezam, Mahmoud; Shar, Muhammad Ali; Umeda, Junko; Kondoh, Katsuyoshi
Abstract: Zirconium effectively became an emerging alloying element used for titanium in order to improve its mechanical properties by Ti grains refinement and solid solution strengthening effects. As a result, Ti-Zr alloy enhances its industrial applications. In this study the titanium powders were sintered after the addition of 2.5 wt% of Zr using Spark Plasma Sintering (SPS) technology. The original pre-mixed powder consists of pure Ti and ZrH2 particles. An applied pressure of 40 MPa and a short sintering time of 5 min were fixed in all experiments under a vacuum of 1 Pascal. EDS, XRD and XPS analysis showed that Zr dispersion as solid solution through α-Ti was homogenized for sintered samples at 1000 °C and 1200 °C while the agglomeration of ZrH2 was detected in the sample sintered at 800 °C. These agglomerated particles reduced the average Zr content through titanium matrix compared to an average of 2.3 to 2.7 wt% for samples sintered at 1000 °C and 1200 °C. The hardness increases with the increase in the sintering temperature. However, since the sample sintered at 1200 °C showed an excessive grain growth that reduced its strength, it was found that 1000 °C sintering temperature can be an optimum temperature for this process.